Insights from five decades of monitoring habitat and breeding populations of American woodcock. Issue 1 (2nd July 2020) - Gutowsky, Sarah Elizabeth; Gutowsky, Lee F.G.; Milton, Gordon Randy; Mallory, Mark L.
Abstract: 1. Habitat loss and degradation are contributing to severe declines in many North American bird species. For American woodcock Scolopax minor ('woodcock'), loss of preferred young forest habitat matrices are generally attributed as the primary drivers of range‐wide population declines in eastern North America, but regional patterns in abundance or habitat availability have not been assessed in Nova Scotia, the northeastern‐most portion of the range. 2. Our objectives were to (a) identify regions of similar trends over the past five decades, (b) evaluate spatiotemporal relationships in the effect of habitat availability on abundance across the province and (c) provide recommendations for woodcock management priorities in Nova Scotia to target local population declines. 3. Using 50 years of standardised surveys and habitat measures, we investigated woodcock population trends and local habitat availability by applying a novel spatially‐explicit model with Integrated Nested Laplace Approximation. 4. Province‐level declines were primarily driven by losses of breeding woodcock in the north and south of the province, while the central region experienced growth. The proportion of area around a survey route comprised of clear‐cut, harvested forest was the most important habitat feature of nine potential explanatory variables to affect abundance, where higher levels of clear‐cut area predicted higher abundance, particularly in the last 15 years (increase from two to 10 birds on average as the amount of clear‐cut area increased from zero to 28%). 5. Historically, habitat for species requiring open areas and regenerating forests would be established through periodic natural disturbance. Today, it is impractical for these processes to occur unimpeded, thus commercial timber harvests and proactive habitat management are necessary to ensure habitat availability. For woodcock in Nova Scotia, partnering with both the local forest products industry and wider national and international habitat management initiatives to provide habitat in the southern and northern regions of the province could be key to improving the population status both locally and ultimately range wide. The temporally and spatially extensive surveys used here provide a remarkably comprehensive avian monitoring dataset. Coupled with modern analytical tools, our study system serves as an example of how long‐term avian survey efforts are capable of informing management regionally to achieve broader conservation targets. Abstract : Province‐level declines of singing American woodcock detected along singing ground survey (SGS) routes from 1968‐2019 were found to be driven primarily by losses in the northeast and southwest, while central regions of the province experienced growth. We then assessed the effect of local habitat availability on woodcock counts along SGS routes by applying a spatially‐explicit model across three distinct time periods. Of nine potential explanatory habitat variables, models showed that the proportion of area around a SGS route comprised of clear‐cut, harvested forest best predicted abundance. Higher levels of clear‐cut area predicted higher levels of abundance, particularly in the last 15 years where the number of singing males detected along a route increased on average from two to 10 birds as clear‐cut area increased from zero to 28%.